Positron Emission Tomography and Magnetic Resonance Imaging of Cellular Inflammation in Patients with Abdominal Aortic Aneurysms. Issue 4 (April 2016) - McBride, O.M.B.; Joshi, N.V.; Robson, J.M.J.; MacGillivray, T.J.; Gray, C.D.; Fletcher, A.M.; Dweck, M.R.; van Beek, E.J.R.; Rudd, J.H.F.; Newby, D.E.; Semple, S.I.
Abstract : Objectives: Inflammation is critical in the pathogenesis of abdominal aortic aneurysm (AAA) disease. Combined 18 F-fludeoxyglucose ( 18 F-FDG) positron emission tomography with computed tomography (PET-CT) and ultrasmall superparamagnetic particles of iron oxide (USPIO)-enhanced magnetic resonance imaging (MRI) are non-invasive methods of assessing tissue inflammation. The aim of this study was to compare these techniques in patients with AAA. Materials and methods: Fifteen patients with asymptomatic AAA with diameter 46 ± 7 mm underwent PET-CT with 18 F-FDG, and T2*-weighted MRI before and 24 hours after administration of USPIO. The PET-CT and MRI data were then co-registered. Standardised uptake values (SUVs) were calculated to measure 18 F-FDG activity, and USPIO uptake was determined using the change in R2*. Comparisons between the techniques were made using a quadrant analysis and a voxel-by-voxel evaluation. Results: When all areas of the aneurysm were evaluated, there was a modest correlation between the SUV on PET-CT and the change in R2* on USPIO-enhanced MRI ( n  = 70, 345 voxels; r  = .30; p  < .0001). Although regions of increased 18 F-FDG and USPIO uptake co-localised on occasion, this was infrequent (kappa statistic 0.074; 95% CI 0.026–0.122). 18 F-FDG activity was commonly focused in the shoulder region whereas USPIO uptake was more apparent in the main body of the aneurysm. Maximum SUV was lower in patients with mural USPIO uptake. Conclusions: Both 18 F-FDG PET-CT and USPIO-MRI uptake identify vascular inflammation associated with AAA. Although they demonstrate a modest correlation, there are distinct differences in the pattern and distribution of uptake, suggesting a differential detection of macrophage glycolytic and phagocytic activity respectively.